Organizational Readiness and its Role in Developing the Managerial Skills of Managers in the National and Iraqi Insurance Companies - Sabah Ibrahim, Maha (2020)
The objective of the research was to determine the role of organizational readiness in the development of management skills from the point of view of a sample of managers in the insurance companies of Aloni and Iraqi and the number of 37 directors, and was based on the questionnaire as a main tool in the collection of data and information, and was analyzed based on the statistical program (SPSS) In extract search results. The research reached the main conclusions: 1) There is a positive and positive relationship between organizational readiness and managerial skills. 2)  There is a significant effect between organizational readiness and managerial skills.